Resort spatiality : reimagining sites of mass tourism - Cantillon, Zelmarie (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"This book theorises resorts as distinct kinds of urban milieux, capturing the complexity of destinations famous for 'sun, sand and sex' mass tourism. Drawing on qualitative field research (participant observation, interviews and photography), the book discusses examples from six international resort destinations spread across four continents: the Gold Coast, Australia; Phuket and Koh Phangan, Thailand; Cancún, Mexico; Miami, USA; and Ibiza, Spain. This volume reviews the material and symbolic production of lived spaces in these resorts, considering the mutually constitutive, mutually transformative relations between their spatial formations, built environments, popular imaginaries, representations, narratives of identity, rhythms, and the experiences and practices of both tourists and locals. In doing so, it argues for more nuanced ways of conceptualising tourism, globalisation and spatiality, reimagining how these phenomena unfold in lived spaces. Taking a cultural studies approach to urban analysis, the book demonstrates the value in embracing complexity, fluidity, partiality and uncertainty. It will be of interest to students and researchers of tourism, geography, cultural studies, development studies, anthropology and sociology"--
Introduction: spatiality and mass tourism -- Resort cities and regions: historical perspectives and contemporary developments -- Popular imaginaries, stereotypes and representations -- Culture and tourism: global trends, local specificity and the symbolic economy -- Living in sites of leisure: local experiences and impacts of tourism -- The right to the city: stratification and belonging among resort residents -- Conclusion: mobilising difference and complexity.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Social aspects; Tourism -- Planning; Resorts -- Social aspects; Spatial behavior; BUSINESS & ECONOMICS / Industries / General; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism